Improving Youth Preparedness in Facing Floods and Landslides Through the Team Games Tournament Method: Peningkatan Kesiapsiagaan Remaja Dalam Menghadapi Bencana Banjir dan Tanah Longsor Melalui Team Games Tournament Method - Yunanto, Rismawan Adi; Prastiani, Ananda Eka; Amalia, Syifa; Ningrum, Teysya Dwi; Salsabila, Kirana Putri; Kristiana, Ike; Febrianti, Fadya; Nafsi, Ayu Ghinan (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
The most frequent disasters in Jember are floods. The most severely affected area is Panti District. The flash floods and landslides in Panti sub-district in 2006 resulted in loss of life and large property losses. This is caused by bare forest vegetation, steep slope topography, and prolonged high rainfall. The population that is vulnerable to disasters is youth. The purpose of this study was to increase youth preparedness knowledge at MTs SA Miftahul Ulum, Sodong Hamlet, Kemiri Village, Panti District in dealing with floods and landslides. The method of providing education is carried out by means of a Team Games Tournament (TGT). Evaluation was carried out using a one group pre-test post-test design. The results obtained were that the value of youth preparedness knowledge significantly increased (p-value <0.001). The TGT method has proven to be effective in increasing disaster preparedness knowledge because the absorption of the material is easier to understand and accept and students are more active in participating during the process of delivering the material.